Development of Learning Applications for Physical Education, Sports, and Health Sepak Takraw Material for High School Students - Helmi, Meutia; Iyakrus, Iyakrus; Hartati, Hartati (Department of Physical Education, Sport, Health and Recreation, 2024)
This research has produced a web-based Sepak Takraw learning media. This research aims to determine the feasibility and effectiveness of web-based Sepak Takraw learning media. This type of research is Research and Development (R&D) using the Sugiyono development method. The development procedure includes identifying potential and issues, data collection, product design, design validation, design revision, product testing, product revision, usage testing, product revision, and limited production. In results, this web-based learning media product for Sepak Takraw is considered suitable for learning, based on the validation results from subject matter experts, with an average rating of 3.7, categorized as “very valid,” and from media experts, with an average rating of 3.27, tagged as “valid.” In small-scale field trials, it received an average rating of 4.65, categorized as “very good.” In large-scale field trials, it received an average rating of 4.82, also classified as “very good” for practical testing. Effective testing was also conducted with 47 students, which resulted in an average N(gain) score of 0.848, categorized as “high,” and an N(gain) score percentage of 84.8%, classified as “effective.” The effectiveness of the web-based Sepak Takraw learning media is shown by the improvement in students’ learning outcomes based on pretest and posttest evaluation data.